Habits of Devotion : Catholic Religious Practice in Twentieth-Century America - O'Toole, James M., 1950- (Book collections on Project MUSE., 2004)
"For generations, American Catholics ... lived out their faith through countless unremarkable routines. Deep questions of theology usually meant little to them, but parishioners clung to deeply ingrained habits of devotion, both public and private. Particular devotions changed over time, waxing or waning in popularity, but the habits endured: going to mass on Sunday, saying prayers privately and teaching their children to do the same, filling their homes with crucifixes and other religious images, participating in special services, blending the church's calendar of feast and fast days with the secular cycles of work and citizenship, negotiating their conformity (or not) to the church's demands regarding sexual behavior and even diet ... It was religious practice, carried out in daily and weekly observance, that embodied their faith, more than any abstract set of dogmas."--The IntroductionIn Habits of Devotion, four senior scholars take the measure of the central religious practices and devotions that by the middle of the twentieth century defined the "ordinary, week-to-week religion" of the majority of American Catholics. Their essays investigate prayer, devotion to Mary, confession, and the Eucharist as practiced by Catholics in the United States before and shortly after the Second Vatican Council. Contributors: Joseph P. Chinnic, O.F.M., Franciscan School of Theology; Paula M. Kane, University of Pittsburgh; Margaret M. McGuinness, Cabrini College; James M. O'Toole, Boston College